MODEL MENTAL MAHASIWA BARU DALAM MEMAHAMI KONSEP STRUKTUR ATOM DITINJAU DARI PENGETAHUAN AWAL - Sunyono, Sunyono; Yuanita, Leny; Ibrahim, Muslimin (Universitas Negeri Surabaya, 2014)
Several studies have shown that mental models can affect a student's ability to perform reasoning on external representation faced. Student mental models are generally used to thinking in order to solve the problem. This study aims to look at the characteristics of mental models beginning of students in understand the concept of atomic structure. Samples were taken at random from the students of Department of Mathematics and Natural Sciences, class of 2012 with the grouping based on students' prior knowledge. The number of samples involved as many as 72 people consisting of students with the prior knowledge of high, medium, and low. Diagnostic tests are used to see the essays shaped the emergence of mental models. The results showed that for all groups of prior knowledge, mental models beginning of students in understand the concept of atomic structure is still dominated by verbal mental model with the category of